Connection through cultivation: a comprehensive design for St. James Place community garden - Brewster, Ashley (Kansas State University, 2015)
Many cities around the United States struggle with racially segregated neighborhoods (USA on Race 2013). The existence of isolated neighborhoods continues to reinforce racial distrust and promotes stereotypes. Some of the primary negative consequences associated with residential segregation include unequal job opportunities, greater health risk, high concentrations of poverty, educational constraints, and high building and lot vacancy rates. Residential segregation is an issue in Kansas City, Missouri along Troost Avenue. Troost Avenue is a stark racial dividing line within the city core. West of Troost Avenue, whites account for 88 percent of the population while blacks make up 93 percent of the population to the east (Troost Village Community Association 2013). The intent for this project is to create a resource to help establish and promote social interaction within the Troost Avenue neighborhoods by creating a purpose-driven community garden at the St. James Place apartment complex. The site’s unique location, positioned adjacent to other apartment complexes and subdivisions in the Citadel Neighborhood, had the potential to attract many types of users to the garden site. Through a process of literature review, surveys, interviews, and precedent study analysis, design goals were established. The design proposals for the St. James Place Community Garden focus on increasing site activity, establishing accessibility, and promoting originality.
Keywords: Community gardens; Troost avenue, Kansas City, MOSocial Interaction; Landscape Architecture (0390)